Karakter Morfologi Rambut Kelompok Cervidae Indonesia - Ni Luh Putu Rischa Phadmacanty; Zulkurnia Irsaf; Gono Semiadi (Jurnal Sain Veteriner, 2020)
Identification through animal hair character is one of a very important forensic tool given the high level of animal trade in Indonesia, one of which is the deer family (Cervidae). Indonesia has four species of Cervidae, there are Rusa timorensis (Javan deer), Rusa unicolor (Sambar deer), Muntiacus muntjak (Barking deer) and Axis kuhlii (Rusa Bawean). Until now, no information about the morphological character of Indonesian cervidae’s hair. In this study, we used 30 shaft/individual/species from Javan deer (8 individuals), Sambar deer (5 individuals), Barking deer (5 individuals) and Bawean deer (5 individual) from specimens collection of Museum Zoologicum Bogoriense (MZB) and field collections. Hairs were analyzed for macroscopic and microscopic, with several parameters of morphology, cuticular structure, medula, cross-section, and medullary index. The result showed that the special character of this family was filled lattice medulla structure and can be used for species  identification.